The Reality of Public School Principals Applying Governance Standards to Gifted Programmes in the Eastern Region, from their Own Perspective - Qatnah, Al-Shammari, fathi, Abunasser Samiah Al-Ghamdi, Badrya, Moaed Al-Otaibi,Samerasaeed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The study aims to identify the degree of male and female school principals applying governance standards (partnership, transparency and accountability) to gifted programmes at the intermediate level in public schools within the eastern region. Furthermore, it attempts to identify differences between governance standards that might be attributed to gender, academic qualification, and management experience. The study adopted the descriptive survey approach due to it being propitious to the nature of the study. After checking the psychometric features of the governance standard scale, a questionnaire was applied to the study sample of 50 male and female principals of public schools at the intermediate level within the directorate of education in the eastern region. Data were processed using arithmetic means, correlation coefficients, the T test, and ANOVA.The findings revealed that both types of principals scored “high” in applying governance standards to gifted students’ programmes. The “partnership” standard was “highest”, while “transparency” and “accountability” standards were equal. Moreover, the findings revealed that there were differences with statistical significance at the function level (a = ≤ 0.05) in favour of females’ application of governance standards, but there was no difference with statistical significance pertaining to the variables of experience and academic qualification among the sample members.